Caracterização de linfócitos B1 na colite desenvolvida por camundongos deficientes para IL-10 - Amanda de Castro Habka (2022)
Inflammatory bowel diseases (IBD) are chronic inflammatory diseases that affect the gastrointestinal tract. There are two main clinical forms of IBD: Crohn's disease (CD) and ulcerative colitis (UC). In general, these diseases are characterized by having a dysregulated inflammatory response against the resident microbiota. Although the exact etiopathogenesis is not clearly defined, several factors have already been identified as capable of contributing strongly to the development of diseases, which can be subdivided into the following categories: genetic factors, factors related to the individual's immune system and environmental factors. In fact, several experimental models used to study IBD have already demonstrated that different flaws in this system lead to the development of colitis and that the absence of the microbiota prevents its appearance. One of these models, characterized by the use of genetically modified mice deficient for IL-10, is particularly important since part of the world population that develops colitis has mutations related to this gene, resulting in the spontaneous development of the disease in a similar way to the experimental model, which also develops spontaneously. In 2012, our group characterized new immunological changes that converge in the development of colitis in IL-10-deficient mice. Interestingly, there was a significant increase in a poorly studied cell in colitis, the B1 lymphocyte. The B1 lymphocyte can be divided into two general populations by the expression (or not) of the CD5 surface marker. But within these populations, there are subpopulations with different surface markers and characteristics. Therefore, the objective of this work was to analyze the subpopulations of B1 lymphocytes in relation to the development of the disease. Our results suggest that the intestinal microenvironment in colitis generates intense and continuous signals that culminate in an increase in the frequency of B2 lymphocytes in Peyer's patches and of B1a PC1lo lymphocytes in the colonic lamina propria. As there was no increase in the frequency of the population of B1a PC1hi lymphocytes, which would be the population capable of secreting IL-10 under normal conditions, the involvement of the other two populations of B lymphocytes mentioned seems to contribute to the exacerbation of the intestinal inflammatory process, even if they are also compensatory mechanisms for the absence of other regulatory mechanisms.